Lithuania’s Economic Growth: Long-Term Strategic Decisions - Vasiliauskas, Aleksandras (Ekonomika, 2002)
The article concisely summarizes the basic long-term strategic decisions of the economic growth in the strategy for development Lithuania’s economy. The draft of that strategy was prepared by scientific expert groups (the author of this article was one of the methodical guides) formed under the Ministry of National Economy by the resolution of the Government of Republic of Lithuania. An attempt is made to describe briefly the basic results of the SWOT analysis (strengths, weaknesses of and opportunities, threats for Lithuania’s economy), the vision of national economy, the state mission for national economic development, the basic strategic goals, the economic reforms and the state policy ensuring the strategy implementation.